Water Quality Monitoring and Assessment System Along Tigris River in Mosul City - Fawaz Y. Abdullah; Mohammad T. Yaseen; Amina A. Fadhil (Tikrit Journal of Engineering Sciences)
This paper aims to address the issue of water pollution in the Tigris River in Mosul city through continuous water quality monitoring. The proposed solution involves the use of LoRa-WAN wireless technology. Wireless sensor nodes would be placed at various stations along the river in Mosul, transmitting data to a LoRa gateway at the Nineveh Water Directorate. This gateway would then communicate with a server via a Cloud platform on the internet. The study utilized the OMNET++ program to simulate data transfer from sensor nodes to the LoRa gateway. Two main contributions are highlighted: an environmental contribution in providing data on water pollution levels and a technological contribution in utilizing the LoRa network for water quality monitoring. Thirteen parameters were measured at nine river stations. The sensor nodes will send notifications to the LoRa-WAN network if any parameter exceeds a predetermined value. The simulations analyzed the received signal strength indicator and packet delivery ratio with 117 sensor nodes managed by one LoRa gateway, covering a 20km area. The LoRa-WAN technology demonstrated satisfactory results in the simulated scenarios, improving network performance by studying the impact of increasing distance between sensor nodes and the gateway on RSSI values for different transmitting power levels (2-14 dBm).